Editorial - Thomas, Joby (Atna Journal of Tourism Studies, 2015)
Atna, Journal of Tourism Studies (AJTS) has offered a platform for the publication of quality articles on research and learning in tourism over the years, thus reading out to researchers and professionals in the field. The Journal has continued to make serious inroads to understand the varied aspects and issues related to the study of tourism. Scholars, with the submission of excellent articles and reviewers through their critical feedback have helped to enhance the quality of the articles published. We are grateful to all authors and reviewers for helping AJTS to build a quality journal among the travel and tourism community in our country. The scholarly contributions featured in the current issue range across such wide areas, as Tourism Development, Local Community and Tourism, Coastal Tourism, Human Resource Management in Tourism, Tourism Management and Heritage Tourism. “A Study on Creation and Development of Wine Tourism Circuits in Maharashtra, by Anupama Kotur Kaddi examines the most important considerations for the creation of wine tourism circuits and analyses the opinions of wine tourism service providers on the creation and development of wine tourism circuits in the wine regions of Maharashtra. Local Community Involvement in Tourism: A Content Analysis of Websites of Wildlife Resorts, by Nagarjuna G reports on the various activities and practices adopted by wildlife resorts for the development of the local community. “Sustainable Coastal Tourism: A Community Perspective,” by Joseph P D and Pakkeerappa P examines the indicators of coastal sustainability from the perspective of the local community along the selected beaches of Dakshina Kannada. Cheryl Venan Dias and Venan Bonaventure Dias try to identify the human resource issues which are prevalent in the micro, small and medium travel, tourism and hospitality enterprises in their article “A Shift from Work-Life Balance to Work-Life Choices: A Study on Tourism Professionals in Goa”.